Strengths and challenges of the first prelicensure baccalaureate of science in nursing program in Pakistan. - Gul RB; Paul P; Olson JK (Journal of Professional Nursing)
With the increasing complexities of health care and the associated strong advocacy for baccalaureate of science in nursing (BScN) program as entry to practice in the developing countries, gradually, nurse leaders are moving in that direction. Although extensive information is available in the literature about the outcomes of prelicensure BScN programs in developed countries, little is known about the outcomes of such programs in developing countries. In this article, we report strengths and challenges of the first prelicensure BScN program in Pakistan. Using a focused ethnographic approach, data for this study were collected mainly through semistructured interviews of the graduates from the first five cohorts of the BScN program and their supervisors at Aga Khan University, Pakistan. Interviews were tape-recorded, transcribed verbatim, and content analyzed for explicit and implicit patterns of themes, meanings, and understanding about the program. Findings of this study affirmed the worth of BScN program for preparing competent nurses that can contribute to the development of nursing in Pakistan. However, various contextual issues and challenges in the nurses work environment have affected the utilization and retention of these graduates and hence the perceived outcome of the program. © 2009 Elsevier Inc.